Empowerment of Posyandu Cadres in the Implementation of Atraumatic Care Approach: Swaddle and Sponge Bath to Optimize Neonatal Adaptation in Pangururan - Tambunan, Dior Manta; Silaen, Harsudianto; Simanullang, Rostime Hermayerni; Buaton, Kristina; Lumbantobing, Dikki Samuel (Proceedings of the International Conference on Nursing and Health Sciences, 2024)
Neonates experience transition from the intrauterine to the extrauterine environment which can cause stress and have long-term consequences on the development of the infant’s brain. One of the neglected and traumatic neonatal care is bathing. Objective: The objective of this community service is to increase the knowledge level of posyandu cadres and the communities about the application of the atraumatic care approach: swaddle and sponge bath to optimize neonatal adaptation. Method: The implementation method is with pre- and post-tests, cadre briefings, health education and demonstration of the swaddle bath method at the Sait Nihuta Village Hall, Pangururan District. This activity was attended by 6 posyandu cadres, 25 community members which are mothers with infants aged 0-5 months, pregnant women, and mothers planning to have their first/next child). Results: It was found that the pre-test knowledge level of posyandu cadres was low in 3 people (50%) and the post-test knowledge level of posyandu cadres was good for 4 people (66.7%). While the pretest knowledge level of community was low in 14 people (56%) and the posttest knowledge level of community was good in 15 people (60%). Conclusions: It can be concluded that there is a significant increase in knowledge level on posyandu cadres and the community about the implementation of the atraumatic care approach: swaddle and sponge bath to optimize neonatal adaptation. Reccomendation: It is expected that the program will continue through cadres who have been provided with education through materials and demonstrations that have been given to the community.